Future and past negative time perspective influences on job satisfaction and organizational commitment in Mexico and the United States. (21st November 2016) - Cernas Ortiz, Daniel Arturo; Davis, Mark A.
Abstract : Purpose: This paper aims to examine the influence of future and past negative time perspectives on job satisfaction and organizational commitment. The effect of national culture (Mexico versus the USA) as a moderator of the above baseline relationships is also analyzed. Design/methodology/approach: The research model is tested using survey data drawn from a sample of 287 Mexican and 274 US MBA students ( N = 561). Regression analyses were used to test the hypotheses. Findings: Future time perspective has a positive relationship with job satisfaction and organizational commitment. Past negative time perspective has a negative association with both job attitudes. The effect of future time perspective on job satisfaction was significantly stronger in Mexico than in the USA. No other significant differences between the countries were found in terms of the time perspective and job attitudes association. Practical implications: The results have implications for managing dispositions that affect work-related attitudes and behaviors with consequences for organizational effectiveness. Originality/value: The findings suggest that time perspective affects job attitudes. Further, they also suggest that the interplay between future time perspective and culture influences job satisfaction.